Effects of fentanyl-propofol co-induction and maintenance with constant rate infusion of dexmedetomidine-fentanyl-lignocaine-ketamine along with variable rate infusion of propofol in dexmedetomidine-midazolamketamine premedicated dogs - Sadali, Roshna; Sooryadas, S.; Remya, V.; Narayanan, M.K.; Jineshkumar, N.S.; David, P. Vinu; Dinesh, P.T. (Indian Journal of Veterinary Surgery, 2025)
The study was conducted in 10 apparently healthy adult dogs categorised as ASA class I or II without considering age and gender presented for elective surgeries. After premedication with meloxicam (0.2 mg/kg body wt.), all the animals were sedated with dexmedetomidine (2 mcg/kg body wt.), midazolam (0.2 mg/ kg body wt.), and ketamine (3 mg/kg body wt.) given intravenously. Upon sedation, co-induction was done intravenously using fentanyl (5 mcg/kg body wt.) followed by propofol administered ‘to effect’. After intubation and oxygensupplementation, lignocaine (2 mg/kg body wt.) was given as a loading dose. Anaesthesia was maintained using a constant rate infusion (CRI) of dexmedetomidine 2 mcg/kg/hr), fentanyl (5 mcg/kg/hr), lignocaine (50 µg/kg/min), and ketamine (40 µg/ kg/min) along with a variable rate infusion of propofol, titrated as needed. Sedation was achieved within 2.10±0.46 min, and anaesthetic maintenance lasted between 86 min and 239 min. Recovery was smooth in 90% of cases, occurring within 13.30±3.84 min after cessation of CRIs. Profound muscle relaxation, analgesia, and unconsciousness were achieved. A transient reduction in heart rate, respiratory rate, and blood pressure was observed postinduction, but mean arterial blood pressure remained adequate for tissue perfusion. In five animals with post-induction apnoea, fluctuations in the end-tidal carbon dioxide (ETCO‚ ) and tidal volume indicated respiratory depression, necessitating assisted ventilation. To conclude, the balanced TIVA protocol demonstrated a safe, effective, and well-tolerated anaesthetic approach for canine surgical patients.